2011
DOI: 10.1007/s11064-011-0455-9
|View full text |Cite
|
Sign up to set email alerts
|

Salicylate Initiates Apoptosis in the Spiral Ganglion Neuron of Guinea Pig Cochlea by Activating Caspase-3

Abstract: Salicylate-induced ototoxicity leading to sensorineural hearing loss (SNHL) and tinnitus is well documented. However, the exact mechanisms are poorly defined. Caspase-3 is a member of the class of effector caspases and has been activated in nearly every model of apoptosis. To examine its role in salicylate-induced injury, we subjected guinea pigs to treatment with a specific inhibitor zDEVD-FMK via the round window niche (RWN) followed by a systemic injection of salicylate at a dose of 200 mg · kg(-1) · d(-1) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…Gene expression analysis and caspase labeling indicated that SGN and nerve fiber degeneration occurred by apoptosis (Wei et al, 2010). More recent in vivo results also indicate that SGN in adult guinea pigs degenerate via caspase-mediated apoptosis after long term treatment with high doses of SS (Feng et al, 2011; Feng et al, 2010). Taken together, these results indicate that SS treatment not only causes damage to SGNs in the developmental stage but also in adult animals.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…Gene expression analysis and caspase labeling indicated that SGN and nerve fiber degeneration occurred by apoptosis (Wei et al, 2010). More recent in vivo results also indicate that SGN in adult guinea pigs degenerate via caspase-mediated apoptosis after long term treatment with high doses of SS (Feng et al, 2011; Feng et al, 2010). Taken together, these results indicate that SS treatment not only causes damage to SGNs in the developmental stage but also in adult animals.…”
Section: Resultsmentioning
confidence: 93%
“…Although high dose SS has been reported to cause hair cell damage (Feng et al, 2010), we and others have not observed hair cell degeneration in vitro or in vivo (Chen et al, 2010; Huang et al, 2005; Wei et al, 2010; Yu et al, 2008; Zheng et al, 1996). On the other hand, prolonged, high-dose SS treatment can permanently reduce the neural output of the cochlea (i.e., CAP) by either inducing apoptosis in SGN or impairing neural function (Chen et al, 2010; Feng et al, 2011; Wei et al, 2010). …”
Section: Discussionmentioning
confidence: 99%
“…As the previous studies described, both the pro- and antiapoptotic genes were involved in neuron survival. Caspase-3 was a crucial mediator of pro-apoptosis for neurons [42]. The overexpression of Bcl-2, which is an antiapoptotic mediator, could promote the neuron survival [43].…”
Section: Discussionmentioning
confidence: 99%
“…Cochlear outer hair cells are the most widely accepted site of injury 4,5). Spiral ganglion cells represent another site of inflammation 6,7). Hypoxia caused by decreased blood flow to the cochlea has also been proposed as a mechanism of injury 8).…”
Section: Discussionmentioning
confidence: 99%